The phrasal verbs variety in the English language - Коляда, Ірина Валеріївна; Суханова, Тетяна Євгенівна (Університет Григорія Сковороди в Переяславі, 2024)
To begin with, it is important to clarify what phrasal verbs are. According to Wikipedia: “A phrasal verb is a verb that consists of a main verb combined with an adverb, a preposition, or both. Usually, their meaning cannot be inferred from the meanings of the individual words themselves. Thousands of phrasal verbs exist and are widely used in the English language. It is estimated that there are at least twenty-five thousand phrasal verbs in English.
Keywords: phrasal verbs; English language; grammar; vocabulary; linguistics